IMPLEMENTATION OF THE ASICC LEARNING MODEL BASED ON LESSON STUDY TO IMPROVE CRITICAL THINKING SKILLS OF STUDENT - Haryati, Rifqi Takriyatu; Putri, Prianka Delvina; Primandiri, Poppy Rahmatika; Budiretnani, Dwi Ari (Jurnal Ilmiah Pendidikan Citra Bakti, 2025)
Critical thinking skills involve logical and reasonable thinking activities that focus on making informed decisions regarding problems faced. Based on the results of observations carried out in class XI-8 SMA Negeri 2 Kediri, the data obtained indicate that the level of critical thinking skills among students is 50.7%. To overcome the problem, an effective learning model is needed to improve students' critical thinking skills, namely the ASICC learning model (Adapting, Searching, Interpreting, Creating & Communicating) which guides students to be able to reflect on themselves to achieve learning objectives, collect key information, solve contextual problems, share ideas, and produce a certain product. The purpose of this study is to determine the improvement of critical thinking skills of class XI-8 students of SMAN 2 Kediri on biology material through the ASICC learning model based on Lesson Study. This study employed a classroom action research (CAR) method, combined with lesson study, as described by Kemmis and McTaggart, and was conducted at SMAN 2 Kediri from February 2025 to March 2025. The data processed shows an increase in students' critical thinking. Data were collected through observations, interviews, post-test questions, and an assessment rubric. This research was analyzed using Zubaidah's Essential Skills of Thinking rubric. This study revealed an increase in students' critical thinking skills, from 62.4% in cycle 1 to 76.8% in cycle 2. Keywords: ASICC, Critical thinking skills